Fund's Income Position for FY 2018 Actual Outcome. (Policy Papers; Policy Paper ;, 2018)
This paper reports the Fund's income position for FY 2018 following the closing of the Fund's accounts for the financial year and completion of the external audit. Total FY 2018 net income, including income from surcharges, amounted to SDR 0.78 billion or SDR 94 million higher than estimated in April, reflecting mainly a larger than anticipated gain reported under IAS 19 (the accounting standard for employee benefits). GRA net income for FY 2018 was about SDR 0.76 billion and has been placed to the Fund's reserves. In accordance with decisions taken in April 2018, a net transfer of currencies amounting to SDR 0.67 billion was made in early August 2018 from the GRA to the Investment Account. The placement of the net income to the Fund's reserves has further strengthened the Fund's precautionary balances, which reached SDR 17.5 billion at the end of FY 2018.